TARIF, KESADARAN DAN SOSIALISASI PAJAK TERHADAP PENINGKATAN PENERIMAAN PAJAK MELALUI KEPATUHAN WAJIB PAJAK SEBAGAI VARIABEL INTERVENING (Implementasi PP 23 Tahun 2018) - Walid Rudianti (Medikonis, 2021)
ABSTRACT This research is motivated by several things. In 2019 the UMKM tax sector is still far below the target (PP 23 is not very influential) and observations that researchers have made in the Banjarnegara District area, show that many MSME do not know about the implementation of the new PP 23 2018 tariff. This research method uses quantitative methods with data collection techniques through distributing questionnaires. Sampling was done by using simple random sampling technique. Hypothesis testing uses regression analysis of mediating variables with the causal step method. The results showed that partially the tariff has a significant positive effect on increasing tax revenue. awareness does not have a significant positive effect on increasing tax revenue and tax socialization has a significant positive effect on increasing tax revenue. Furthermore, tariffs have a significant positive effect on taxpayer compliance, awareness has a significant positive effect on taxpayer compliance and tax socialization does not have a significant positive effect on taxpayer compliance. then taxpayer compliance has a significant positive effect on increasing tax revenue. for taxpayer compliance mediates the relationship between rates and increased tax revenue. Taxpayer compliance does not mediate the relationship between taxpayer awareness and increased tax revenue. and taxpayer compliance mediates the relationship between tax socialization and increased tax revenue.